Closure of the Paleo‐Asian Ocean in the Middle‐Late Triassic (Ladinian‐Carnian): Evidence From Provenance Analysis of Retroarc Sediments. Issue 14 (22nd July 2021) - Song, Dongfang; Xiao, Wenjiao; Windley, Brian F.; Mao, Qigui; Ao, Songjian; Wang, Hao Y. C.; Li, Rui
Abstract: A major current debate in Asian tectonics concerns the time of closure of the Paleo‐Asian Ocean (PAO) and the collision between the Central Asian arcs and the Tarim and North China cratons (NCC). This has led to much uncertainty about the reconstruction of proto‐Asia and tectonic configuration of northeast Pangea. Here we report Triassic provenance change in the foreland of the Alxa Block by field‐based zircon U‐Pb and Hf isotopic analysis. Nonmarine sediments, unconformable on or in fault contact, with the Alxa basement yield Precambrian and Paleozoic–Triassic detrital zircon ages with maximum depositional ages of Middle‐Late Triassic (∼244–224 Ma). Hf isotopic data indicate that Middle Triassic sandstones were sourced from the NCC basement and a continental arc, whereas Late Triassic sediments received an additional input from a juvenile arc. This provenance change in the foreland sedimentation indicates that the final closure of the PAO was in the Middle‐Late Triassic. Plain Language Summary: The Central Asian Orogenic Belt, the world's largest Phanerozoic accretionary orogen, was constructed by the amalgamation of magmatic arcs and subduction‐accretion complexes during the protracted subduction of the Paleo‐Asian Ocean (PAO). The collision between Central Asian arcs and the Tarim and North China cratons led to the final closure of the PAO and formation of proto‐Asia and northeast Pangea. Constraining when and how the PAO closed is fundamental for a better understanding of the complex history of assembly of this part of Asia and the process from accretion to collision of the accretionary orogen. We conducted geological mapping and provenance analysis of a newly discovered foreland deposition on the Alxa Block in northwest China. The results reveal a provenance change in the Middle‐Late Triassic, which we interpret as a response to collision between the juvenile Central Asian arcs and the North China Craton. Our findings combined with regional data point to final closure of the PAO in the Middle‐Late Triassic. Key Points: Discovery of Triassic syn‐orogenic sediments in the foreland of the Alxa Block, northwest China Detrital zircon U‐Pb and Lu‐Hf isotopic data indicate that juvenile Central Asian arc detritus arrived in the Alxa foreland by Carnian The provenance change constrains the time of closure of the Paleo‐Asian Ocean as Middle‐Late Triassic (Ladinian‐Carnian)